Diagnostic accuracy of Non-ECG Gated Chest CT (NEGCT) for cardiac chambers’ dimensions in comparison with echocardiography: Non-ECG Gated Chest CT (NEGCT) for cardiac chambers’ dimensions (Journal of Fatima Jinnah Medical University, 2023)
Objective: To analyze the accuracy of Non-ECG Gated Chest CT (NEGCT) for cardiac chambers’ dimensions, keeping Echocardiography as the gold standard.Methods: After IRB approval, all patients that underwent concurrent contrast chest CT/CTPA and transthoracic 2D echocardiography exam at our institute within 1 month interval comprised the study population. Data was archived from HMIS PACS Database. The sizes of right ventricle (RV), left ventricle (LV) and left atrium (LA) was recorded in shot axis at axial CT sections and at echocardiography. RV and LV-transverse diameter was measured at basal third of the heart, from the inner to inner myocardium perpendicular to the inter-ventricular septum and LA-max. Anterior-posterior dimension was measured at the level of the aortic root.Results: Total 213 subjects were studied, with average age of 52.1±15.8 years. The CT-Echocardiography measurement concordance rates were significantly high for LA, LV and RV measuring 93.8%, 96.7% and 69.01% respectively. Using CT threshold for LA, LV, RV enlargement > or equal to 45, 55, 35mm, the AUC via ROC curve analysis was estimated to be 0.912, 0.992, 0.650 respectively. The sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and diagnostic accuracy of NEGCT was found to be 66.67%, 95.10%, 37.5%, 98.5% and 93.90% for LA; 100%, 96.67%, 30.0%, 100%, 96.7% for LV and 33.33%, 74.86%, 17.86% 87.26% and 69.01% for RV respectively.Conclusion: Overall, the accuracy of chamber dimensions at NEGCT was excellent with high CT-Echocardiography concordance, making it an alternative modality for examining chamber sizes, in the absence of cardiac MRI. Through it, a radiologist can also add more value to CT reporting.Keywords:      Echocardiography, NEGCT, Dimensional Measurement
Keywords: Echocardiography; EGCT; Dimensional Measurement